2021
DOI: 10.3390/cancers13122944
|View full text |Cite
|
Sign up to set email alerts
|

Response to Androgens and Androgen Receptor Antagonists in the Presence of Cytokines in Prostate Cancer

Abstract: Non-steroidal anti-androgens have a major role in the treatment of non-localized prostate cancer. Interleukins are involved in the regulation of many cellular functions in prostate cancer and also modify cellular response to anti-androgens. A specific role of selected IL is presented in this review. IL-8 is a cytokine expressed in prostate cancer tissue and microenvironment and promotes proliferation and androgen receptor-mediated transcription. In contrast, IL-1 displays negative effects on expression of andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Neutralization of hypoxia‐regulated proteins (IL‐8 and VEGF) inhibits enzalutamide‐induced tumor growth. Culig 32 suggested that IL‐8 is inversely correlated with AR, and that IL‐8 might regulate the neuroendocrine phenotype in PCa. Our data supported that the IL‐8 secretion derived from the interaction between PCa cells and prostate fibroblasts induces not only the expression of AR‐V7, but also that of NSE.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of hypoxia‐regulated proteins (IL‐8 and VEGF) inhibits enzalutamide‐induced tumor growth. Culig 32 suggested that IL‐8 is inversely correlated with AR, and that IL‐8 might regulate the neuroendocrine phenotype in PCa. Our data supported that the IL‐8 secretion derived from the interaction between PCa cells and prostate fibroblasts induces not only the expression of AR‐V7, but also that of NSE.…”
Section: Discussionmentioning
confidence: 99%
“…maintenance of cell activation and survival signals. AR is also activated by Jak/STAT signaling pathway through IL-6 and possibly other cytokines [53][54][55]. MAP kinase and cytokine signaling pathways also activates the nuclear factor "kappalight-chain-enhancer" of activated B-cells (NF-κB) pathway, which has been implicated in various cancers including prostate cancer.…”
Section: Pca and Androgen Signalingmentioning
confidence: 99%
“…Moreover, activation of the androgen receptor by IL-6 in some subtypes of PC is associated with increased growth of tumor cells in vitro and in vivo . It has been reported that some molecules such as niclosamide and gallilactone can be very effective in simultaneously inhibiting the STAT3 pathway as well as the androgen receptor ( 44 ). The synergistic effect of TGF-β and epidermal growth factor (EGF) has also been shown to lead to the metastasis of tumor cells to the bone in PC.…”
Section: Involved Cytokines In the Pathogenesis Of Pcmentioning
confidence: 99%